Electrode, battery, and method of producing electrode
The electrode structure with a defined distribution of void particles and open pores addresses the rate characteristic issues in existing battery materials, improving electron and ion transport and reducing gas generation for better battery performance.
Patent Information
- Application Number
- KR1020250134729
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-09-20
- Filing Date
- 2025-09-18
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-18
AI Technical Summary
Existing positive electrode materials in batteries, such as those combining lithium iron manganese phosphate (LMFP) and high-nickel layered oxide, do not adequately address rate characteristics, which are crucial for performance.
A positive electrode structure is designed with a specific distribution of void particles and open pores, where the ratio of vacant particles in the first region to the total is 50% or more, and open pore particles are between 40% to 95% of the vacant particles, enhancing electron and ion pathways.
This structure improves the rate characteristics of the battery by facilitating efficient electron and ion transport while reducing gas generation, leading to enhanced performance.
Smart Images

Figure 112025107325841-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present disclosure relates to an electrode, a battery, and a method for manufacturing an electrode. Background Technology
[0002] International Publication No. 2020 / 261879 discloses that the positive electrode active material comprises lithium iron manganese phosphate (LMFP) and a high-nickel layered oxide, wherein the average particle size of the secondary particles of the LMFP is 3 nm or more and 20 nm or less.
[0003] Various types of positive electrode active materials have been developed to improve battery characteristics. Patent Document 1 provides a positive electrode (battery) that combines energy density and safety by mixing a high-nickel layered oxide with excellent energy density and an LMFP with excellent safety. However, there is still room for improvement in the rate characteristics.
[0004] The purpose of the present disclosure is to improve rate characteristics.
[0005] The technical configuration and effects of the present disclosure are described below. However, the mechanism of action of the present disclosure includes presumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0006] [1] Includes a collecting foil and a positive electrode layer,
[0007] The above positive electrode layer is disposed on the surface of the above current collector foil, and
[0008] The above positive electrode layer includes a positive electrode active material, and
[0009] The above positive electrode active material includes a plurality of secondary particles, and
[0010] Each of the plurality of the above secondary particles comprises a plurality of primary particles, and
[0011] The above secondary particle includes a void particle having a void, and
[0012] The cross-section of the above positive electrode layer includes a first region and a second region, and
[0013] The first region and the second region are distinguished by the cross-section of the positive electrode layer being divided into two equal parts in the thickness direction, and
[0014] The first region is disposed between the current collector and the second region, and
[0015] The relationship 50%≤X is satisfied, and
[0016] The above X represents the ratio of the vacant particles included in the first region to the vacant particles included in the first region and the second region, and
[0017] In the above-mentioned vacancy particle having a maximum ferret diameter of 5 μm or more, wherein X is calculated,
[0018] electrode.
[0019] The secondary particles include vacancy particles having vacancies. An electrode containing such vacancy particles is expected to have improved rate characteristics compared to a high-density electrode. In addition, the cross-section of the positive electrode layer includes a first region and a second region. The first region can be rephrased as "deep" or "deep layer." The first region is positioned on the side relatively closer to the current collector foil compared to the second region. The second region can be rephrased as "shallow" or "surface layer." Since the relationship 50% ≤ X is satisfied, an efficient electron path or ion path is formed, and thus an improvement in rate characteristics is expected.
[0020] [2] The relationship 60%≤X is satisfied,
[0021] Electrode described in [1].
[0022] With the relationship 60%≤X satisfied, further improvement in rate characteristics is expected.
[0023] [3] The above-mentioned pore particles include open pore particles in which the pores are open to the outside, and
[0024] The relationship 40%≤Y≤95% is satisfied, and
[0025] The above Y represents the ratio of the open pore particles to the above vacant particles, and
[0026] In the above-mentioned vacancy particles having a maximum ferret diameter of 5 μm or more, the above-mentioned Y is produced,
[0027] Electrode described in [1] or [2].
[0028] Possible particles include open-pore particles having pores that are open to the outside, and closed-pore particles (hollow particles) in which pores are not open to the outside. Here, if the electrode has many pores, there is a possibility that the electrode active material and the electrolyte will react and gas will be generated. This can occur when closed-pore particles are included in a certain proportion. Therefore, a reduction in the amount of gas generated is expected by satisfying the relationship 40% ≤ Y ≤ 95%.
[0029] [4] The relationship 60%≤Y≤80% is satisfied,
[0030] Electrode described in [3].
[0031] With the relationship 60%≤Y≤80% satisfied, a reduction in gas generation is expected.
[0032] [5] Each of the above primary particles comprises an olivine-type phosphate compound,
[0033] Electrode described in any of [1] to [4].
[0034] [6] The above olivine-type phosphate compound is lithium iron manganese phosphate,
[0035] Electrode described in [5].
[0036] [7] Including an electrode described in any one of [1] to [6],
[0037] battery.
[0038] [8] Having a bipolar structure,
[0039] [7] The battery listed in [7].
[0040] [9] (a) Preparing the positive electrode active material,
[0041] (b) contacting at least a portion of the above positive electrode active material with a first solvent,
[0042] (c) Forming a slurry by mixing the positive electrode active material after contact with the first solvent and the second solvent,
[0043] (d) applying the above slurry to the surface of the current collector foil, and,
[0044] (e) forming a positive electrode layer by drying the above slurry, comprising,
[0045] The above positive electrode active material includes a plurality of secondary particles, and
[0046] The above secondary particle includes a void particle having a void, and
[0047] The first solvent has a higher boiling point compared to the second solvent,
[0048] Method for manufacturing an electrode.
[0049] It is expected that the electrode described in [1] will be manufactured by undergoing the manufacturing process described in [9] above.
[0050]
[10] In the above (c), the positive electrode active material after contact with the first solvent and the positive electrode active material not contacted with the first solvent are weighed in a mass ratio of 1:0 to 1:2 and the second solvent is mixed.
[0051] Method for manufacturing electrodes as described in [9].
[0052]
[11] The first solvent above contains N-methyl-2-pyrrolidone, and
[0053] The second solvent above includes water,
[0054] [9] or
[10] Method for manufacturing an electrode.
[0055] Hereinafter, one embodiment of the present disclosure (hereinafter abbreviated as “this embodiment”) and one example of the present disclosure (hereinafter abbreviated as “this example”) are described. However, this embodiment and this example do not limit the technical scope of the present disclosure. This embodiment and this example are illustrative in all respects. This embodiment and this example are non-limiting. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description in the claims. For example, any configuration may be derived from this embodiment, and any combination thereof is also intended from the outset.
[0056] The above and other objects, features, aspects, and advantages of this invention will become apparent from the following detailed description of this invention as understood in conjunction with the accompanying drawings. Brief explanation of the drawing
[0057] FIG. 1 is a schematic cross-sectional view showing an electrode in the present embodiment. FIG. 2 is a conceptual diagram showing secondary particles in the present embodiment. FIG. 3 is a schematic flowchart illustrating a method for manufacturing an electrode in the present embodiment. FIG. 4 is a schematic perspective view of a battery in the present embodiment. Figure 5 is a schematic cross-sectional view along line VI-VI in Figure 4. Figure 6 is a table showing the manufacturing conditions and experimental results of the positive electrode in the example. Figure 7 is the temperature profile during firing. Specific details for implementing the invention
[0058] < Terms and Phrases >
[0059] "Equipped with," "includes," "possesses," and variations thereof are open-ended expressions. A configuration expressed as open-ended may include additional elements in addition to the essential elements, or it may not include them. The description "consists of" is a closed-ended expression. However, even a configuration expressed as closed may include additional elements that are incidental in normal circumstances or are unrelated to the subject technology. The description "substantially consists of..." is a semi-closed expression. In a configuration expressed as semi-closed, the addition of elements that do not substantially affect the fundamental and novel characteristics of the subject technology is permitted.
[0060] Expressions such as "may" and "can" are used not in an obligatory sense meaning "must do," but in a permissive sense meaning "having the possibility to do."
[0061] Unless otherwise specifically stated, the execution order of multiple steps, actions, and operations included in various methods is not limited to the order described. For example, multiple steps may proceed simultaneously. For example, multiple steps may be sequential.
[0062] Expressions such as “first,” “second,” etc., are used solely to distinguish multiple elements from one another. Such expressions do not limit the elements to which they are attached in any way. Such expressions are unrelated to, for example, the order or importance of the elements to which they are attached.
[0063] For example, the expression “at least one of A and B” includes “A or B” and “A and B”. “At least one of A and B” may also be written as “A and / or B”.
[0064] Geometric terms should not be interpreted in a strict sense. Examples of geometric terms include "parallel," "perpendicular," and "orthogonal." For instance, directions, angles, distances, etc., may be relatively displaced within the scope of achieving substantially the same or similar functions. Geometric terms may include tolerances and errors, such as those arising from design, operation, or manufacturing. The dimensional relationships in the drawings may not correspond to actual dimensional relationships. To aid the reader's understanding, dimensional relationships in the drawings may be altered. For instance, lengths, widths, thicknesses, etc., may be changed. Some components may also be omitted.
[0065] Elements described in the “singular form” may also include the plural form unless otherwise specifically stated. For example, particles may refer to multiple particles, a collection of particles, and a separated body.
[0066] Numerical ranges such as “m to n%” include upper and lower limits unless specifically stated otherwise. That is, “m to n%” represents a numerical range of “m% or more and n% or less.” Furthermore, “m% or more and n% or less” includes “greater than m% and less than n%.” “greater than” and “less than or equal to” are indicated by inequality signs “≤, ≥” with an equal sign. “greater than” and “less than” are indicated by inequality signs “<, >” without an equal sign. A numerical value arbitrarily selected from within the numerical range may become a new upper or lower limit. For example, a new numerical range may be established by arbitrarily combining a numerical value within the numerical range with a numerical value described in other parts of this specification, tables, drawings, etc.
[0067] All numerical values are modified by the term "approximately." The term "approximately" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the form of use of the subject technology. All numerical values may be expressed in significant figures. Unless otherwise specified, the measurement value may be the average of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. Generally, the reliability of the average value is expected to improve as the number of measurements increases. The measurement value may be rounded to the nearest whole number based on the number of significant figures. The measurement value may include errors, for example, due to the detection limits of the measuring device.
[0068] The devices, software, etc. used for measuring various values are merely examples. Equivalent products to the devices exemplified may be used. If equivalent products are used, the measurement conditions may be adjusted to suit the device.
[0069] The ratio of vacant particles in the first region (X) and the ratio of open pore particles (Y) to vacant particles in the first and second regions are measured in the following order. The electrode is cut at an arbitrary location. By doing so, a cross-sectional sample of the positive electrode layer is obtained. The electrode may be a monopolar electrode (positive electrode) or a bipolar electrode, as long as it includes the positive electrode layer. For example, ion milling treatment is performed on the cross-sectional sample. The cross-sectional sample is observed by a scanning electron microscope (SEM). The observation magnification may be adjusted within a range of, for example, 5,000 to 15,000 times (for example, 10,000 times). In multiple fields of view (for example, about 5 fields of view), vacant particles in the first and second regions, vacant particles in the first region, and open pore particles in the first and second regions are counted. Among the vacant particles and open pore particles, those having a maximum ferret diameter of 5 μm or more are counted. "X" is obtained by dividing the number of vacant particles included in the first region by the number of vacant particles included in the first region and the second region. "Y" is obtained by dividing the number of open pore particles included in the first region and the second region by the number of vacant particles included in the first region and the second region.
[0070] The "maximum ferret diameter" of a particle represents the length of the long side of the circumscribed rectangle (rectangle or square) of the particle. If the circumscribed rectangle is square, the length of the long side represents the length of one side. The maximum ferret diameter of the secondary particle can be measured in the SEM image described above. The maximum ferret diameter of the primary particle can be measured, for example, in a Transmission Electron Microscopy (TEM) image.
[0071] "D50" indicates the particle size at which the cumulative value is 50% in the volume-based particle size distribution (cumulative distribution). The volume-based particle size distribution is measured by a laser diffraction particle size distribution measuring device.
[0072] The stoichiometric composition formula represents a representative example of the compound. The compound may have a non-stoichiometric composition. For example, "Al2O3" is not limited to a compound having a substance ratio (molar ratio) of "Al / O = 2 / 3". Unless otherwise specified, "Al2O3" refers to a compound containing Al and O in any substance ratio. For example, the compound may be doped with trace elements. Some of the Al and O may be substituted with other elements.
[0073] The chemical composition of the compound can be measured by ICP-AES (Inductively coupled plasma atomic emission spectroscopy). A sample solution is prepared by dissolving 0.1 g of a sample (e.g., a positive electrode active material) in a mixed acid (10 ml) of hydrochloric acid and sulfuric acid. The sample solution is diluted to an appropriate concentration using a volumetric flask. After dilution, compositional analysis is performed using an ICP-AES device. For example, the product name "PS3520 UVDD II (manufactured by Hitachi High-Tech Science Co., Ltd.)" may be used.
[0074] "Derivative" refers to a compound that has been modified in part of the parent compound by at least one selected from the group consisting of the introduction of a functional group, substitution of an atom, oxidation, reduction, and other chemical reactions. The modification site may be one site or multiple sites. "Substituents" are, for example, alkyl groups, alkenyl groups, alkynyl groups, cycloalkyl groups, unsaturated cycloalkyl groups, aromatic groups, heterocyclic groups, halogen atoms (F, Cl, Br, I, etc.), OH groups, SH groups, CN groups, SCN groups, OCN groups, nitro groups, alkoxy groups, unsaturated alkoxy groups, amino groups, alkylamino groups, dialkylamino groups, aryloxy groups, acyl groups, alkoxycarbonyl groups, acyloxy groups, aryloxycarbonyl groups, acylamino groups, alkoxycarbonylamino groups, aryloxycarbonylamino groups, sulfonylamino groups, sulfamoyl groups, carbamoyl groups, alkylthio groups, arylthio groups, sulfonyl groups, sulfinyl groups, ureido groups, phosphate amide groups, sulfo groups, carboxyl groups, hydroxamic acid groups, sulfino groups, hydrazino groups, imino groups, and, It may include at least one selected from the group consisting of silyl groups, etc. These substituents may be further substituted. If there are two or more substituents, the substituents may be identical or different. Multiple substituents may be combined to form a ring.
[0075] Electrode
[0076] FIG. 1 is a schematic cross-sectional view showing an electrode in the present embodiment. The electrode (110) may be, for example, a positive electrode of a monopolar battery. The cross-section of FIG. 1 is parallel to the thickness direction (Z direction) of the electrode (110). The electrode (110) includes a current collector foil (113) and a positive electrode layer (11).
[0077] The current collector foil (113) is a conductor. The current collector foil (113) supports the positive electrode layer (11). The current collector foil (113) may be in the form of a sheet, for example. The thickness of the current collector foil (113) may be, for example, 1 to 50 μm, 3 to 30 μm, or 5 to 15 μm. The current collector foil (113) has conductivity. The current collector foil (113) may include, for example, a metal foil, etc. The current collector foil (113) may include at least one type selected from the group consisting of, for example, Cu, Ni, Zn, Pb, Al, Ti, Fe, Ag, Au, and a conductive resin. The current collector foil (113) may include, for example, an Al foil, an Al alloy foil, etc. The current collector foil (113) may have a multilayer structure, for example. For example, the current collector foil (113) may be formed by joining the Al foil and the Cu foil.
[0078] The positive electrode layer (11) is disposed on the surface of the current collector foil (113). The positive electrode layer (11) may be disposed on only one side of the current collector foil (113). The positive electrode layer (11) may be disposed on both sides of the current collector foil (113). When the electrode (110) is a bipolar battery, the positive electrode layer (11) may be disposed on one side (front side) of the current collector foil (113), and a negative electrode layer (not shown) may be disposed on the other side (back side). For example, a groove may be formed in the positive electrode layer (11). The positive electrode layer (11) may be formed in a stripe shape, for example. The thickness of the positive electrode layer (11) may be, for example, 10 μm or more, 100 μm or more, 200 μm or more, 400 μm or more, 600 μm or more, 800 μm or more, or 1 mm or more. The thickness of the positive electrode layer (11) may be, for example, 1.2 mm or less, 1 mm or less, or 800 μm or less. In the case of a bipolar structure, a thick positive electrode layer (11) of 200 μm or more may be required.
[0079] The positive electrode layer (11) contains a positive electrode active material. That is, the electrode (110) contains a positive electrode active material.
[0080] FIG. 2 is a conceptual diagram showing secondary particles in the present embodiment. The positive electrode active material includes a plurality of secondary particles (2). The secondary particles (2) are an aggregate of primary particles (1). That is, the secondary particles (2) include a plurality of primary particles (1). The secondary particles (2) include a porous particle (2c) having a pore (3) and a non-porous particle (2d) not having a pore (3). The porous particle (2c) includes an open pore particle (2a) having an open pore (3a) through which the pore (3) is connected to the outside, and a closed pore particle (2b) (hollow particle) through which the pore (3) is not connected to the outside. The pore of the closed pore particle (2b) is also called a void (3b). In addition, in the SEM image, the non-porous particle (2d) may also have a pore (3) at a location that is not visible in the SEM image. However, in this embodiment, the presence or absence of the void (3) is determined by the appearance in the SEM image alone.
[0081] In the 30 secondary particles (2), the average value of the maximum ferret diameter may be, for example, 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more. The average value of the maximum ferret diameter may be, for example, 30 μm or less, 25 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less.
[0082] The secondary particle (2) may have a spherical shape. By the secondary particle (2) being spherical, an improvement in packing efficiency is expected, for example. The sphericity of the secondary particle (2) may be 0.85 or higher, 0.90 or higher, or 0.95 or higher. The sphericity of the secondary particle (2) may be, for example, 1 or lower, 0.95 or lower, or 0.90 or lower. "Sphericity" refers to the circularity in a surface SEM image (two-dimensional image). Sphericity (circularity) is calculated by the following formula.
[0083] ψ=4πS / L 2
[0084] ψ: Sphericity (Circularity)
[0085] π: Pi
[0086] S: Cross-sectional area of the secondary particle (2) (area of the region enclosed by the contour of the secondary particle (2))
[0087] L: Peripheral length of the secondary particle (2) (length of the contour of the secondary particle (2))
[0088] Sphericity represents the arithmetic mean of 30 secondary particles (2).
[0089] For 30 primary particles (1), the average value of the maximum ferret diameter may be, for example, 10 to 90 nm. That is, the maximum ferret diameter of the primary particles (1) may be, for example, 10 to 90 nm. The maximum ferret diameter of the primary particles (1) may be, for example, 20 nm or more, 30 nm or more, 40 nm or more, 50 nm or more, 60 nm or more, 70 nm or more, or 80 nm or more. The maximum ferret diameter of the primary particles (1) may be, for example, 80 nm or less, or 60 nm or less.
[0090] A carbon layer (4) may be attached to the surface of the primary particle (1). The carbon layer (4) contains carbon (C). The amount of the carbon layer (4) attached may be, for example, 0.1% or more, 0.5% or more, 1% or more, 2% or more, 3% or more, or 4% or more in mass fraction relative to the secondary particle (2). The amount of the carbon layer (4) attached may be, for example, 5% or less, 4% or less, or 3% or less in mass fraction relative to the secondary particle (2).
[0091] Each of the plurality of primary particles (1) may include, for example, an olivine-type phosphate compound, a layered lithium metal complex oxide, etc. "Olivine-type" represents a crystal structure belonging to the space group Pnma. "Layered-type" represents a crystal structure belonging to the space group R-3m. The space groups are identified by X-ray diffraction (XRD) measurement. The primary particles (1) may be, for example, single-phase compounds. The primary particles (1) may further include, for example, an amorphous phase, etc.
[0092] The olivine-type phosphate compound may include, for example, lithium iron phosphate (LFP), lithium manganese phosphate (LMP), etc. In LMP, some of the manganese (Mn) may be substituted with iron (Fe). The Fe substituent of LMP is also described as LMFP. LMP may have a composition represented, for example, by the following general formula.
[0093] Li 1-a Mn 1-x Fe x PO4
[0094] For example, the relationship -0.5 ≤ a ≤ 0.5 may be satisfied. The amount of Fe substitution (x) may be, for example, 0 or more, 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. The amount of Fe substitution (x) may be, for example, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.
[0095] In the LMP, elements other than lithium (Li), Mn, Fe, phosphorus (P), and oxygen (O) (dopants) may be doped. The doping amount (the fraction of the amount of substance relative to the amount of substance of Li) may be, for example, 0.01 to 0.1. Dopants are, for example, boron (B), nitrogen (N), halogen, silicon (Si), sodium (Na), magnesium (Mg), aluminum (Al), chromium (Cr), scandium (Sc), titanium (Ti), vanadium (V), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), gallium (Ga), germanium (Ge), selenium (Se), strontium (Sr), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), indium (In), lead (Pb), bismuth (Bi), antimony (Sb), tin (Sn), tungsten (W), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), It may include at least one selected from the group consisting of dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and actinoids.
[0096] Layered lithium metal composite oxides may include, for example, lithium nickel composite oxide (LNO), lithium cobalt composite oxide (LCO), lithium manganese composite oxide (LMO), etc.
[0097] LNO may have a composition represented by, for example, the following general formula.
[0098] Li 1-a Ni x M 1-x O2
[0099] In the equation, the relationships -0.5≤a≤0.5 and 0≤x≤1 are satisfied. M may include, for example, at least one type selected from the group consisting of Co, Mn and Al. For example, the relationships 0<x≤0.1, 0.1≤x≤0.2, 0.2≤x≤0.3, 0.3≤x≤0.4, 0.4≤x≤0.5, 0.5≤x≤0.6, 0.6≤x≤0.7, 0.7≤x≤0.8, 0.8≤x≤0.9, or 0.9≤x≤1 may be satisfied. For example, the relationships -0.4≤a≤0.4, -0.3≤a≤0.3, -0.2≤a≤0.2, or -0.1≤a≤0.1 may be satisfied.
[0100] LNO is, for example, LiNi 0.9 Co 0.1 O2, LiNi 0.9 Mn 0.1 It may include at least one selected from the group consisting of O2 and LiNiO2.
[0101] LNO may be represented, for example, by the following general formula. A compound represented by the following general formula may also be called "NCM".
[0102] Li 1-a Ni x Co y Mn z O2
[0103] In the equation, the relationships -0.5≤a≤0.5, 0<x<1, 0<y<1, 0<z<1, and x+y+z=1 are satisfied. For example, the relationships 0<x≤0.1, 0.1≤x≤0.2, 0.2≤x≤0.3, 0.3≤x≤0.4, 0.4≤x≤0.5, 0.5≤x≤0.6, 0.6≤x≤0.7, 0.7≤x≤0.8, 0.8≤x≤0.9, or 0.9≤x<1 may be satisfied. For example, the relationship 0<y≤0.1, 0.1≤y≤0.2, 0.2≤y≤0.3, 0.3≤y≤0.4, 0.4≤y≤0.5, 0.5≤y≤0.6, 0.6≤y≤0.7, 0.7≤y≤0.8, 0.8≤y≤0.9, or 0.9≤y<1 may be satisfied. For example, the relationship 0<z≤0.1, 0.1≤z≤0.2, 0.2≤z≤0.3, 0.3≤z≤0.4, 0.4≤z≤0.5, 0.5≤z≤0.6, 0.6≤z≤0.7, 0.7≤z≤0.8, 0.8≤z≤0.9, or 0.9≤z<1 may be satisfied.
[0104] NCM is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2, LiNi 0.3 Co 0.4 Mn 0.3 O2, LiNi 0.3 Co 0.3 Mn 0.4 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi 0.5 Co 0.4 Mn 0.1 O2, LiNi 0.5 Co 0.1 Mn 0.4 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.6 Co 0.3 Mn0.1 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.7 Co 0.2 Mn 0.1 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, and, LiNi 0.9 Co 0.05 Mn 0.05 It may include at least one type selected from the group consisting of O2.
[0105] LNO may be represented, for example, by the following general formula. A compound represented by the following general formula may also be called "NCA".
[0106] Li 1-a Ni x Co y Al z O2
[0107] In the equation, the relationships -0.5≤a≤0.5, 0<x<1, 0<y<1, 0<z<1, and x+y+z=1 are satisfied. For example, the relationships 0<x≤0.1, 0.1≤x≤0.2, 0.2≤x≤0.3, 0.3≤x≤0.4, 0.4≤x≤0.5, 0.5≤x≤0.6, 0.6≤x≤0.7, 0.7≤x≤0.8, 0.8≤x≤0.9, or 0.9≤x<1 may be satisfied. For example, the relationship 0<y≤0.1, 0.1≤y≤0.2, 0.2≤y≤0.3, 0.3≤y≤0.4, 0.4≤y≤0.5, 0.5≤y≤0.6, 0.6≤y≤0.7, 0.7≤y≤0.8, 0.8≤y≤0.9, or 0.9≤y<1 may be satisfied. For example, the relationship 0<z≤0.1, 0.1≤z≤0.2, 0.2≤z≤0.3, 0.3≤z≤0.4, 0.4≤z≤0.5, 0.5≤z≤0.6, 0.6≤z≤0.7, 0.7≤z≤0.8, 0.8≤z≤0.9, or 0.9≤z<1 may be satisfied.
[0108] NCA is, for example, LiNi 0.7 Co 0.1 Al 0.2 O2, LiNi 0.7 Co 0.2 Al 0.1 O2, LiNi 0.8 Co 0.1 Al 0.1 O2, LiNi 0.8 Co 0.17 Al 0.03 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, and, LiNi 0.9 Co 0.05 Al 0.05 It may include at least one type selected from the group consisting of O2.
[0109] The positive electrode active material may include both an olivine-type phosphate compound and a layered lithium metal composite oxide. The mixing ratio (mass ratio) of the olivine-type phosphate compound and the layered lithium metal composite oxide may be, for example, “olivine-type phosphate compound / layered lithium metal composite oxide = 9 / 1 to 1 / 9”, “olivine-type phosphate compound / layered lithium metal composite oxide = 8 / 2 to 2 / 8”, “olivine-type phosphate compound / layered lithium metal composite oxide = 7 / 3 to 3 / 7”, or “olivine-type phosphate compound / layered lithium metal composite oxide = 6 / 4 to 4 / 6”.
[0110] The positive electrode layer (11) includes a first region (111) and a second region (112). The positive electrode layer (11) may consist of a first region (111) and a second region (112). Each region may form a layer. The first region (111) and the second region (112) are distinguished by the cross-section of the positive electrode layer (11) being divided into two equal parts in the thickness direction. That is, the area fraction of the first region (111) and the second region (112) relative to the entire positive electrode layer (11) is 50% each. The first region (111) is positioned between the current collecting foil (113) and the second region (112). The first region (111) is in direct contact with the current collecting foil (113). The first region (111) includes the interface between the current collector foil (113) and the positive electrode layer (11). The second region (112) includes the surface of the positive electrode layer (11). That is, the second region (112) is exposed to the surface of the positive electrode layer (11).
[0111] In the positive polar layer (11), the relationship represented by the following formula is satisfied.
[0112] 50%≤X
[0113] The above X represents the ratio of the vacant particles (2c) included in the first region (111) to the vacant particles (2c) included in the first region (111) and the second region (112). The above X is calculated for vacant particles (2c) having a maximum ferret diameter of 5 μm or more.
[0114] An electrode containing vacant particles (2c) is expected to have improved rate characteristics compared to a high-density electrode. Also, since the relationship “50%≤X” is satisfied, an electron pass or ion pass is efficiently formed, so an improvement in rate characteristics is expected.
[0115] X may be 55% or more, 60% or more, 65% or more, 70% or more, or 75% or more. X may be 100% or less, 95% or less, 90% or less, 85% or less, or 80% or less. By satisfying the relationship “60%≤X”, further improvement in rate characteristics is expected.
[0116] In the positive polarity layer (11), the relationship represented by the following formula may be satisfied.
[0117] 40%≤Y≤95%
[0118] The above Y represents the ratio of open pore particles (2a) to pore particles (2c). The above Y is calculated for pore particles (2c) having a maximum ferret diameter of 5 μm or more.
[0119] When the electrode has many pores (3), the electrode active material and the electrolyte may react, and gas may be generated. This can occur when the electrode contains a certain proportion of closed pore particles. Therefore, a reduction in the amount of gas generated is expected when the relationship 40% ≤ Y ≤ 95% is satisfied.
[0120] Y may be 45% or more, 50% or more, 55% or more, 60% or more, or 65% or more. Y may be 90% or less, 85% or less, 80% or less, 75% or less, 70% or less, or 65% or less. By satisfying the relationship “60%≤Y≤80%”, a reduction in the amount of gas generated is expected to be greater.
[0121] The positive electrode layer (11) may further include, for example, a conductive material, a binder, and a thickening material in addition to the positive electrode active material. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material. The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of graphite, acetylene black (AB), Ketjen black (registered trademark), vapor-grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake (GF).
[0122] The amount of binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of positive electrode active material. The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), carboxymethylcellulose (CMC), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyoxyethylene alkyl ether, and derivatives thereof. SBR, CMC, PAA, and PVP, etc., may also function as thickeners.
[0123] The positive electrode layer (11) may further include, for example, an inorganic filler, an organic filler, a solid electrolyte, a surface modifier, a dispersant, a lubricant, a flame retardant, a protective agent, a flux, a coupling agent, an adsorbent, etc. The positive electrode layer (11) may also include, for example, polyoxyethyleneallylphenyl ether phosphate, a zeolite, a silane coupling agent, MoS2, WO3, etc.
[0124] Method for manufacturing electrodes >
[0125] FIG. 3 is a schematic flowchart illustrating a method for manufacturing an electrode in the present embodiment. Hereinafter, the “method for manufacturing an electrode in the present embodiment” may be abbreviated as “the present method.” The present method may include, for example, “(a) a preparation process,” “(b) a contact process,” “(c) a mixing process,” “(d) a coating process,” and “(e) a drying process.”
[0126] (a) Preparation process
[0127] This process is a process for preparing a positive electrode active material. Below, the case of manufacturing LMFP as the positive electrode active material is described as an example. However, the positive electrode active material in this disclosure is not limited to LMFP.
[0128] (a-1) Slurry formation
[0129] The present process may include forming a slurry by mixing a lithium compound, a manganese compound, an iron compound, a phosphate compound, and a solvent. For example, the compositional formula "Li 1-a Mn 1-x Fe x The lithium compound, manganese compound, iron compound, and phosphate compound may be weighed such that the composition ratio (amount of substance ratio) is as shown in PO4(-0.5≤a≤0.5, 0≤x<1). The lithium compound may include, for example, lithium hydroxide. The manganese compound may include, for example, manganese carbonate. The iron compound may include, for example, ferric phosphate. The phosphate compound may include, for example, lithium dihydrogen phosphate.
[0130] When a carbon layer is formed on the surface of the primary particles, a carbon raw material is added to the raw material mixture. The carbon raw material may include, for example, sugars, organic acids, etc. The carbon raw material may include, for example, glucose, sucrose, fructose, citric acid, etc. The amount of carbon raw material added may be, for example, 1 to 20% by mass fraction relative to the raw material mixture.
[0131] The solvent may include, for example, water. The solid content concentration of the slurry may be, for example, 20 to 40% by mass fraction. The proportion of secondary particles having open pores can be adjusted by adjusting the solid content concentration of the slurry.
[0132] The particle size in the slurry may be adjusted by performing wet grinding. For example, wet grinding may be performed so that the D50 is 0.10 to 1 μm.
[0133] (a-2) Assembly
[0134] The process may include aggregating secondary particles by drying the slurry. For example, secondary particles may be aggregated by a spray drying method. The size of the secondary particles and the proportion of secondary particles having open pores can be adjusted by adjusting the conditions in the spray dryer. In particular, the intake port temperature may affect the proportion of secondary particles having open pores. The intake port temperature may be, for example, 190°C or higher, 210°C or higher, or 230°C or higher. The intake port temperature may be, for example, 270°C or lower or 250°C or lower.
[0135] The exhaust port temperature may be, for example, 100 to 130°C. The spray rate may be, for example, 5 to 15 mL / min. The intake pressure may be, for example, about 1.8 to 2.2 MPa. The nozzle pressure of the spray nozzle may be, for example, 0.1 to 0.3 MPa.
[0136] (a-3) Sintering
[0137] The process may include generating a positive electrode active material (LMFP) by performing heat treatment on secondary particles. Any heat treatment furnace (e.g., electric furnace, muffle furnace, etc.) may be used. The heat treatment atmosphere may be, for example, an inert atmosphere. The inert atmosphere may be, for example, a nitrogen atmosphere. The heat treatment temperature may be, for example, 400 to 700°C. The heat treatment time may be, for example, 4 to 6 hours. During the heating process for firing, the temperature may not be raised continuously, but the heating may be stopped at around 200°C and the temperature may be maintained at 200°C for about 1 hour.
[0138] (b) Contact process
[0139] The present process is a process of contacting at least a portion of the positive electrode active material obtained in the above (a) preparation process with a first solvent.
[0140] The positive electrode active material obtained in the above (a) preparation process comprises pore particles having pores and non-pore particles not having pores. By contacting the positive electrode active material with a first solvent, the first solvent is filled into the pores of the pore particles. Since the pore particles filled with the first solvent have a higher specific gravity than the non-pore particles, it is thought that they are present in large quantities on the current collector side when coated onto the current collector in the process described later.
[0141] The positive electrode active material may be washed after contact with the first solvent. By doing so, excess first solvent attached to the surface of the positive electrode active material can be removed. For example, the positive electrode active material after contact with the first solvent may be filtered by suction, separated into solid and liquid, and then washed with water.
[0142] The first solvent may include, for example, N-methyl-2-pyrrolidone (NMP), etc. The contact time may be, for example, 6 to 24 hours.
[0143] (c) Mixing process
[0144] This process is a process of forming a slurry by mixing the positive electrode active material after the contact process (b) above and a second solvent.
[0145] For example, a slurry is formed by dispersing the positive electrode active material after the contact process (b) in the second solvent. A conductive material, a binder, and a thickening material may be mixed.
[0146] In addition, a positive electrode active material that has not been brought into contact with the first solvent may be mixed. That is, the positive electrode active material obtained in the preparation process (a) above may be mixed in this process without performing the contact process (b) above. The positive electrode active material after the contact process (b) above and the positive electrode active material that has not undergone the contact process (b) above may be weighed in a mass ratio of 1:0 to 1:2 and mixed with the second solvent. When the proportion of the positive electrode active material after the contact process (b) above is high, it is thought that when coated on the current collector foil in the process described later, the positive electrode active material after the contact process (b) above is present in large quantities on the current collector foil side.
[0147] The second solvent may include, for example, water. The first solvent has a higher boiling point compared to the second solvent. When the boiling point of the first solvent is higher than that of the second solvent, the second solvent evaporates faster than the first solvent when drying in the process described later. As a result, it is believed that a large amount of the positive electrode active material filled with the second solvent exists on the current collector side. In addition, the boiling point of NMP is 202°C, and the boiling point of water is 100°C.
[0148] (d) Coating process
[0149] This process is a process of applying the slurry obtained in the above (c) mixing process to the surface of the current collector foil.
[0150] For example, the slurry may be applied to the surface of the current collector foil by means of a doctor blade or a die coater.
[0151] (e) Drying process
[0152] This process is a process for forming a positive electrode layer by drying the slurry after the (d) coating process above.
[0153] The drying temperature may be, for example, 100°C or higher. After drying, the positive electrode layer may be compressed. By doing so, the density of the positive electrode layer can be adjusted.
[0154] Liquid Battery
[0155] In some of the present embodiments, the battery is a liquid-based battery. The liquid-based battery includes an electrolyte. In some of the present embodiments, the battery has a monopolar structure. In some of the present embodiments, the battery has a bipolar structure. As an example, a battery having a bipolar structure (bipolar battery) is described.
[0156] FIG. 4 is a schematic perspective view of a battery according to the present embodiment. FIG. 5 is a schematic cross-sectional view along line VI-VI in FIG. 4. Hereinafter, "plane-line direction" indicates a normal direction to the surface of a sheet-like member (e.g., foil, electrode, etc.). "Plane-line direction" indicates any direction perpendicular to the plane-line direction. In FIG. 5, the Z-axis direction corresponds to the plane-line direction. The X-axis direction and the Y-axis direction are examples of plane-line directions.
[0157] The battery (100) includes an outer body (90) and a power generation element (50). The outer body (90) houses the power generation element (50). The outer body (90) may include, for example, a first current collector plate (91), a first laminate film (92), a second laminate film (93), and a second current collector plate (94). The first laminate film (92) and the second laminate film (93) are joined together at the ends in the plane direction. At the joint between the first laminate film (92) and the second laminate film (93), a sealing material (not shown) may be interposed between the first laminate film (92) and the second laminate film (93).
[0158] The first collector plate (91) and the second collector plate (94) are bonded to the power generation element (50) at the end of the stacking direction (Z-axis direction). A first laminate film (92) is bonded to the first collector plate (91). A second laminate film (93) is bonded to the second collector plate (94). At the bonding portion between the collector plate and the laminate film, a sealing material (not shown) may be interposed between the collector plate and the laminate film.
[0159] The power generation element (50) includes a plurality of bipolar electrodes (10). The plurality of bipolar electrodes (10) are stacked in a plane-oriented direction (Z-axis direction). Each of the plurality of bipolar electrodes (10) includes a positive electrode layer (11), a bipolar current collector (13), and a negative electrode layer (12) in this order in the plane-oriented direction. In the plane-oriented direction (e.g., X-axis direction), the bipolar current collector (13) extends outward relative to the positive electrode layer (11) and the negative electrode layer (12). For example, the bipolar current collector (13) may extend outward relative to the positive electrode layer (11) and the negative electrode layer (12) over the entire circumference in the plane-oriented direction. The details of the positive electrode layer (11) are as described above.
[0160] The bipolar current collector foil (13) may include, for example, a metal foil, a conductive resin layer, etc. For example, the bipolar current collector foil (13) may be formed by bonding an Al foil and a Cu foil. A carbon material may be coated on the surface of the bipolar current collector foil (13). The carbon material may include, for example, carbon black, etc.
[0161] The power generation element (50) includes a sealing material (30). At the end in the direction in the plane, the sealing material (30) is bonded to the current collecting foil (13). The sealing material (30) may, for example, be heat-welded to the bipolar current collecting foil (13). For example, the sealing material (30) may be arranged along the entire circumference in the direction in the plane. The sealing material (30) may, for example, include a resin material. The sealing material (30) seals the space between adjacent bipolar current collecting foils (13) in the direction in the plane. By sealing the space between the bipolar current collecting foils (13) with the sealing material (30), a cell (40) is partitioned. The cell (40) is the minimum unit of the power generation element (50). The battery (100) may also be called a "bipolar module" because it includes a plurality of cells (40). Each of the plurality of cells (40) is sealed. The plurality of cells (40) are isolated from each other. Each of the plurality of cells (40) includes a positive electrode layer (11), a separator (20), a negative electrode layer (12), and an electrolyte.
[0162] (Polar layer)
[0163] The negative electrode layer (12) is attached to one side of the bipolar current collector foil (13). The negative electrode layer (12) is positioned behind the positive electrode layer (11). The negative electrode layer (12) may have a larger surface area than the positive electrode layer (11). The negative electrode layer (12) contains a negative electrode active material.
[0164] The negative electrode active material may, for example, be in the form of particles or sheets. The D50 of the negative electrode active material may, for example, be 1 μm or more, 5 μm or more, or 10 μm or more. The D50 of the negative electrode active material may, for example, be 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less.
[0165] The negative electrode active material may include any component. The negative electrode active material may include, for example, at least one selected from the group consisting of carbon-based active materials, alloy-based active materials, Si-C composite materials, Li metal, Li-based alloys, and lithium titanate. In some of the present embodiments, the battery may be a Li metal negative electrode battery.
[0166] The carbon-based active material may include at least one selected from the group consisting of, for example, graphite, soft carbon, and hard carbon. "Graphite" is a general term for natural graphite and artificial graphite. Graphite may be a mixture of natural graphite and artificial graphite. The mixing ratio (mass ratio) may be, for example, "natural graphite / artificial graphite = 1 / 9 to 9 / 1", "natural graphite / artificial graphite = 2 / 8 to 8 / 2", or "natural graphite / artificial graphite = 3 / 7 to 7 / 3".
[0167] The surface of the graphite may be coated, for example, with amorphous carbon. The surface of the graphite may be coated, for example, with a heterogeneous material. The heterogeneous material may include, for example, at least one selected from the group consisting of P, W, Al, and O. The heterogeneous material may include, for example, at least one selected from the group consisting of Al(OH)3, AlOOH, Al2O3, WO3, Li2CO3, LiHCO3, and Li3PO4.
[0168] The alloy-based active material may include, for example, at least one selected from the group consisting of Si, Li silicate, SiO, Si-based alloy, tin (Sn), SnO, and Sn-based alloy.
[0169] SiO may be represented, for example, by the following general formula.
[0170] SiO x
[0171] In the equation, the relationship 0 < x < 2 is satisfied. For example, the relationship 0.5 ≤ x ≤ 1.5 or 0.8 ≤ x ≤ 1.2 may be satisfied.
[0172] "Si-C composite material" refers to a composite material of a carbon-based active material (such as graphite) and an alloy-based active material (such as Si). For example, Si fine particles may be dispersed within carbon particles. For example, Si fine particles may be dispersed within graphite particles. For example, Li silicate particles may be coated by a carbon material (such as amorphous carbon).
[0173] (Separator)
[0174] The separator (20) can separate the positive electrode layer (11) from the negative electrode layer (12). The separator (20) has electrical insulation properties. The separator (20) may include, for example, at least one selected from the group consisting of a resin film (polymer film), an inorganic particle layer, and an organic particle layer. The separator (20) may include, for example, a resin film and an inorganic particle layer.
[0175] The resin film is porous. The resin film may include, for example, a microporous film, a nonwoven fabric, etc. The resin film includes a resin backbone. The resin backbone may be continuous in a network form, for example. Pores are formed in the gaps of the resin backbone. The resin film is permeable to an electrolyte. The resin film may have, for example, an average pore diameter of 1 μm or less. The average pore diameter of the resin film may be, for example, 0.01 to 1 μm or 0.1 to 0.5 μm. The "average pore diameter" can be measured by the mercury intrusion method. The Gurley value of the resin film may be, for example, 50 to 250 s / 100 cm³. The "Gurley value" can be measured by the Gurley test method.
[0176] The resin film may comprise at least one selected from the group consisting of, for example, olefin resin, polyurethane resin, polyamide resin, cellulose resin, polyether resin, acrylic resin, and polyester resin. The resin film may comprise at least one selected from the group consisting of, for example, polyethylene (PE), polypropylene (PP), polyamide (PA), polyamideimide (PAI), polyimide (PI), aromatic polyamide (aramid), polyphenylene ether (PPE), and derivatives thereof. The resin film may be formed, for example, by a stretching method, a phase separation method, etc. The thickness of the resin film may be, for example, 5 to 50 μm or 10 to 25 μm.
[0177] The resin film may, for example, have a single-layer structure. The resin film may, for example, be composed of a PE layer. The framework of the PE layer is formed by PE. The PE layer may have a shutdown function. The resin film may, for example, have a multi-layer structure. The resin film may, for example, include a PP layer and a PE layer. The framework of the PP layer is formed by PP. The resin film may, for example, have a three-layer structure. The resin film may, for example, be formed by stacking a PP layer, a PE layer, and a PP layer in this order. The thickness of the PE layer may, for example, be 5 to 20 μm. The thickness of the PP layer may, for example, be 3 to 10 μm.
[0178] The inorganic particle layer may be formed on the surface of the resin film. The inorganic particle layer may be formed on only one side of the resin film or on both sides. The inorganic particle layer may be formed on the surface facing the positive electrode layer (11) or on the surface facing the negative electrode layer (12). Additionally, the inorganic particle layer may be formed on the surface of the positive electrode layer (11) or on the surface of the negative electrode layer (12).
[0179] The inorganic particle layer is porous. The inorganic particle layer contains inorganic particles. The inorganic particles may also be called "inorganic fillers." Pores are formed in the spaces between the inorganic particles. The thickness of the inorganic particle layer may be, for example, 0.5 to 10 μm or 1 to 5 μm. The inorganic particles may include, for example, a heat-resistant material. An inorganic particle layer containing a heat-resistant material is also called a "Heat Resistance Layer (HRL)." The inorganic particles may include at least one selected from the group consisting of boehmite, alumina, zirconia, titania, magnesia, and silica. The inorganic particles may have any shape. The inorganic particles may be, for example, spherical, rod-shaped, plate-shaped, fibrous, etc. The D50 of the inorganic particles may be, for example, 0.1 to 10 μm or 0.5 to 3 μm. The inorganic particle layer may further contain a binder. The binder may include at least one selected from the group consisting of, for example, acrylic resin, polyamide resin, fluorine resin, aromatic polyether resin, and liquid crystal polyester resin.
[0180] The separator (20) may include, for example, an organic particle layer. The separator (20) may include, for example, an organic particle layer instead of a resin film. The separator (20) may include, for example, an organic particle layer instead of an inorganic particle layer. The separator (20) may include both a resin film and an organic particle layer. The separator (20) may include both an inorganic particle layer and an organic particle layer. The separator (20) may include a resin film, an inorganic particle layer, and an organic particle layer.
[0181] The thickness of the organic particle layer may be, for example, 0.1 to 50 μm, 0.5 to 20 μm, 0.5 to 10 μm, or 1 to 5 μm. The organic particle layer contains organic particles. The organic particles may also be called "organic fillers." The organic particles may contain heat-resistant materials. The organic particles may contain at least one selected from the group consisting of, for example, PE, PP, PTFE, PI, PAI, PA, and aramid. The organic particles may be, for example, spherical, rod-shaped, plate-shaped, fibrous, etc. The D50 of the organic particles may be, for example, 0.1 to 10 μm or 0.5 to 3 μm.
[0182] The separator (20) may include, for example, a mixed layer. The mixed layer includes both inorganic particles and organic particles.
[0183] (Electrolyte)
[0184] The electrolyte is a liquid electrolyte. The electrolyte contains a solute and a solvent. The concentration of the solute may be, for example, 0.5 to 1 mol / L, 1 to 1.5 mol / L, 1.5 to 2 mol / L, 2 to 2.5 mol / L, or 2.5 to 3 mol / L. "mol / L" may also be denoted as "M". The solute contains a support salt (Li salt). The solute may contain, for example, an inorganic salt, an imide salt, an oxalato complex, a halide, etc. The solute may include at least one selected from the group consisting of, for example, LiPF6, LiBF4, LiClO4, LiAsF6, LiSbF6, LiN(SO2F)2 "LiFSI", LiN(SO2CF3)2 "LiTFSI", LiB(C2O4)2 "LiBOB", LiBF2(C2O4) "LiDFOB", LiPF2(C2O4)2 "LiDFOP", LiPO2F2, FSO3Li, LiI, LiBr, and derivatives thereof.
[0185] The electrolyte may include, for example, a carbonate-based solvent (carbonate ester-based solvent). The solvent may include, for example, cyclic carbonates, chain carbonates, fluorinated carbonates, etc. The solvent may include, for example, at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (FEC), difluoroethylene carbonate, 4,4-difluoroethylene carbonate, trifluoroethylene carbonate, perfluoroethylene carbonate, fluoropropylene carbonate, difluoropropylene carbonate, and derivatives thereof.
[0186] The solvent may contain cyclic carbonates (EC, PC, FEC, etc.) and chain carbonates (EMC, DMC, DEC, etc.). The mixing ratio (volume ratio) of the cyclic carbonates and chain carbonates may be, for example, “cyclic carbonate / chain carbonate = 1 / 9 to 4 / 6”, “cyclic carbonate / chain carbonate = 2 / 8 to 3 / 7”, or “cyclic carbonate / chain carbonate = 3 / 7 to 4 / 6”.
[0187] The solvent may contain cyclic carbonates (EC, PC, etc.) and fluorinated cyclic carbonates (FEC, etc.). The mixing ratio (volume ratio) of the cyclic carbonate and the fluorinated cyclic carbonate may be, for example, “cyclic carbonate / fluorinated cyclic carbonate = 99 / 1 to 90 / 10”, “cyclic carbonate / fluorinated cyclic carbonate = 9 / 1 to 1 / 9”, “cyclic carbonate / fluorinated cyclic carbonate = 9 / 1 to 7 / 3”, or “cyclic carbonate / fluorinated cyclic carbonate = 3 / 7 to 1 / 9”.
[0188] The solvent may include, for example, EC, FEC, EMC, DMC, and DEC. The volume ratio of each component may satisfy the relationship represented by, for example, the following equation.
[0189] V EC +V FEC +V EMC +V DMC +V DEC = 10
[0190] Among the above formulas, V EC , V FEC , V EMC , V DMC , V DEC represents the volume ratios of EC, FEC, EMC, DMC, and DEC, respectively.
[0191] 1≤V EC ≤4, 0≤V FEC ≤3, V EC +V FEC ≤4,
[0192] 0≤V EMC ≤9, 0≤V DMC ≤9, 0≤V DEC ≤9, 6≤V EMC +V DMC +V DEC ≤9
[0193] The relationship is satisfied.
[0194] For example, 1≤V EC ≤2, or 2≤V EC It is acceptable if the relationship ≤3 is satisfied.
[0195] For example, 1≤V FEC ≤2, or 2≤V FEC It is acceptable if the relationship ≤4 is satisfied.
[0196] For example, 3≤V EMC ≤4, or 6≤V EMC It is acceptable if the relationship ≤8 is satisfied.
[0197] For example, 3≤V DMC ≤4, or 6≤V DMC It is acceptable if the relationship ≤8 is satisfied.
[0198] For example, 3≤V DEC ≤4, or 6≤V DEC It is acceptable if the relationship ≤8 is satisfied.
[0199] The solvent may have a composition in volume ratio such as, for example, “EC / EMC = 3 / 7”, “EC / DMC = 3 / 7”, “EC / FEC / DEC = 1 / 2 / 7”, “EC / DMC / EMC = 3 / 4 / 3”, “EC / DMC / EMC = 3 / 3 / 4”, “EC / FEC / DMC / EMC = 2 / 1 / 4 / 3”, “EC / FEC / DMC / EMC = 1 / 2 / 4 / 3”, “EC / FEC / DMC / EMC = 2 / 1 / 3 / 4”, and “EC / FEC / DMC / EMC = 1 / 2 / 3 / 4”.
[0200] The electrolyte may include an ether-based solvent. The electrolyte may include, for example, at least one selected from the group consisting of tetrahydrofuran (THF), 1,4-dioxane (DOX), 1,3-dioxolane (DOL), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), hydrofluoroether (HFE), ethylglyme, triglyme, tetraglyme, and derivatives thereof.
[0201] The electrolyte may contain any additives. The amount of additive (mass fraction relative to the total electrolyte) may be, for example, 0.01 to 5%, 0.05 to 3%, or 0.1 to 1%. The additives may include, for example, solid electrolyte interphase (SEI) formation promoters, SEI formation inhibitors, gas generators, overcharge prevention agents, flame retardants, antioxidants, electrode protective agents, surfactants, etc.
[0202] Additives include, for example, vinylene carbonate (VC), vinylethylene carbonate (VEC), 1,3-propanesulfone (PS), tert-amylbenzene, 1,4-di-tert-butylbenzene, biphenyl (BP), cyclohexylbenzene (CHB), ethylene sulfite (ES), propanesulfone (PS), ethylene sulfate (DTD), γ-butyrolactone, phosphazene compounds, carboxylic acid esters [e.g., methyl formate (MF), methyl acetate (MA), methylpropionate (MP), diethyl malonate (DEM), etc.], fluorobenzenes (e.g., monofluorobenzene (FB), 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,3,5-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, etc.), fluorotoluene (e.g., 2-fluorotoluene, 3-fluorotoluene, 4-fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,6-difluorotoluene, 3,4-difluorotoluene, octafluorotoluene, etc.), benzotrifluoride (e.g., benzotrifluoride, 2-fluorobenzotrifluoride, 3-fluorobenzotrifluoride, 4-fluorobenzotrifluoride, 2-methylbenzotrifluoride, 3-methylbenzotrifluoride, 4-methylbenzotrifluoride, etc.), fluoroxylene (e.g., 3-fluoro-o-xylene, 4-fluoro-o-xylene, 2-fluoro-m-xylene, 5-fluoro-m-xylene, etc.), sulfur-containing heterocyclic compounds (e.g., benzothiazole, 2-methylbenzothiazole, tetrathiafulvalene, etc.), nitrile compounds (e.g., adiponitrile, succinonitrile, etc.), phosphate esters (e.g., trimethyl phosphate, triethyl phosphate, etc.), carboxylic acid anhydrides (e.g., acetic anhydride, propionic anhydride, oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, benzoic anhydride, etc.), alcohols (e.g., methanol, ethanol,It may include at least one selected from the group consisting of n-propyl alcohol, ethylene glycol, diethylene glycol monomethyl ether, etc.), and derivatives thereof.
[0203] The aforementioned components as solutes and solvents may be used as trace components (additives). The additive may include, for example, at least one selected from the group consisting of LiBF4, LiFSI, LiTFSI, LiBOB, LiDFOB, LiDFOP, LiPO2F2, FSO3Li, LiI, LiBr, HFE, DOX, PC, FEC, and derivatives thereof.
[0204] The electrolyte may contain an ionic liquid. The ionic liquid may contain, for example, at least one selected from the group consisting of sulfonium salts, ammonium salts, pyridinium salts, piperidinium salts, pyrrolidinium salts, morpholium salts, phosphonium salts, imidazolium salts, and derivatives thereof.
[0205] In some of the present embodiments, the battery may include a gel electrolyte. That is, the battery may be a polymer battery. The gel electrolyte may include an electrolyte and a polymer material. The polymer material may form a polymer matrix. The polymer material may include, for example, at least one selected from the group consisting of PVdF, PVdF-HFP, polyacrylonitrile (PAN), PVdF-PAN, polyethylene oxide (PEO), polyethylene glycol (PEG), and derivatives thereof.
[0206] All-solid-state battery
[0207] In some of the present embodiments, the battery is an all-solid-state battery. The all-solid-state battery may have a bipolar structure. The all-solid-state battery includes a solid electrolyte instead of an electrolyte and a separator (20). That is, instead of a separator (20), a solid electrolyte layer separates the negative electrode layer (12) from the positive electrode layer (11). The solid electrolyte layer includes, for example, a solid electrolyte and a binder. The positive electrode layer (11) and the negative electrode layer (12) may also include a solid electrolyte.
[0208] The solid electrolyte may be, for example, a powder. The D50 of the solid electrolyte may be, for example, 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, 0.6 μm or more, 0.7 μm or more, 0.8 μm or more, 0.9 μm or more, or 1 μm or more. The D50 of the solid electrolyte may be 5 μm or less, 4 μm or less, 3 μm or less, 2 μm or less, or 1 μm or less.
[0209] The solid electrolyte may include, for example, at least one selected from the group consisting of sulfide solid electrolytes, halide solid electrolytes, oxide solid electrolytes, hydride solid electrolytes, and nitride solid electrolytes.
[0210] The sulfide solid electrolyte may include at least one selected from the group consisting of an amorphous phase, a crystalline phase, and a glass ceramic (crystallized glass) phase. The crystalline phase may be, for example, an argyrodite type, an LGPS type, etc. The sulfide solid electrolyte includes Li and sulfur (S). In addition to Li and S, the sulfide solid electrolyte may further include any other component.
[0211] Sulfide solid electrolytes are, for example, LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li 10 GeP2S 12 , Li4P2S6, Li7P3S 11 It may include at least one selected from the group consisting of Li3PS4 and Li7PS6.
[0212] For example, "LiI-LiBr-Li3PS4" represents a solid sulfide electrolyte produced by mixing LiI, LiBr, and Li3PS4 in any amount ratio. For example, the solid sulfide electrolyte may be produced by a mechanochemical method. The mixing ratio may be specified by placing a number in front of each raw material. For example, "10LiI-15LiBr-75Li3PS4" indicates that the mixing ratio is "LiI / LiBr / Li3PS4 = 10 / 15 / 75 (amount ratio)."
[0213] The sulfide solid electrolyte may have a composition represented by, for example, the following general formula.
[0214] xLi2S-(1-x)P2S5
[0215] In the formula, x may be, for example, greater than 0, 0.1 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.75 or more, 0.8 or more, or 0.9 or more. x may be, for example, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.75 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less. For example, when x = 0.75, "xLi2S-(1-x)P2S5" may have the composition of Li3PS4.
[0216] The sulfide solid electrolyte may have a composition represented by, for example, the following general formula.
[0217] yLiI-zLiBr-(100-yz)[xLi2S-(1-x)P2S5]
[0218] In the formula, x may be, for example, 0.5 or more, 0.6 or more, 0.7 or more, 0.75 or more, 0.8 or more, or 0.9 or more. x may be, for example, 1 or less, 0.9 or less, 0.8 or less, 0.75 or less, 0.7 or less, or 0.6 or less. y may be, for example, 0 or more, 5 or more, 10 or more, 15 or more, 20 or more, or 25 or more. y may be, for example, 30 or less, 25 or less, 20 or less, 15 or less, 10 or less, or 5 or less. z may be, for example, 0 or more, 5 or more, 10 or more, 15 or more, 20 or more, or 25 or more. z may be, for example, 30 or less, 25 or less, 20 or less, 15 or less, 10 or less, or 5 or less.
[0219] The sulfide solid electrolyte may have a composition represented by, for example, the following general formula.
[0220] Li 7-x-2y PS 6-x-y X y
[0221] In the formula, the relationships “0<7-x-2y”, “0<6-xy”, “0≤x”, and “0≤y” are satisfied. X may include at least one selected from the group consisting of, for example, fluorine (F), chlorine (Cl), bromine (Br), and iodine (I).
[0222] The sulfide solid electrolyte may have a composition represented by, for example, the following general formula.
[0223] Li 4-x M 1-x P x S4
[0224] In the formula, x may be, for example, greater than 0, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. x may be, for example, less than 1, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less. M may include, for example, at least one selected from the group consisting of Al, Zn, In, Ge, Si, Sn, Sb, Ga, and Bi.
[0225] The sulfide solid electrolyte may have a composition represented by, for example, the following general formula.
[0226] Li 10+x Ge 1+x P 2-x S 12
[0227] In the formula, x may be, for example, 0 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more. x may be, for example, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less. The sulfide solid electrolyte represented by the above general formula may include, for example, an LGPS-type crystalline phase.
[0228] The halogenated solid electrolyte may have a composition represented by, for example, the following general formula.
[0229] Li 6-na M a X6
[0230] In the formula, n represents the oxidation number of M. M may include, for example, an atom having an oxidation number of +3. M may include, for example, an atom having an oxidation number of +4. M may include at least one selected from the group consisting of, for example, Y, Al, Ti, Zr, Ca, and Mg. For example, the relationship “0 < a < 2” may be satisfied. X may include at least one selected from the group consisting of, for example, F, Cl, Br, and I.
[0231] The halogenated solid electrolyte may have a composition represented by, for example, the following general formula.
[0232] Li 3-a Ti a Al 1-a F6
[0233] In the formula, a may be, for example, 0 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. a may be, for example, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.
[0234] The halogenated solid electrolyte may have a composition represented by, for example, the following general formula.
[0235] Li3YCl a Br b I 6-a-b
[0236] In the expression, for example, the relationship “0≤a+b≤6” may be satisfied. a may be, for example, 0 or greater, 1 or greater, 2 or greater, 3 or greater, 4 or greater, or 5 or greater. a may be, for example, 6 or less, 5 or less, 4 or less, 3 or less, 2 or less, or 1 or less. b may be, for example, 0 or greater, 1 or greater, 2 or greater, 3 or greater, 4 or greater, or 5 or greater. b may be, for example, 6 or less, 5 or less, 4 or less, 3 or less, 2 or less, or 1 or less.
[0237] Oxide solid electrolytes are, for example, LiNbO3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, La 2 / 3-x Li 3x TiO3 and, Li7La3Zr2O 12 It may include at least one selected from the group consisting of. The hydride solid electrolyte may include, for example, LiBH4. The nitride solid electrolyte may include, for example, Li3N, Li3BN2, etc.
[0238] [Example]
[0239] The Production of Straight Dramas
[0240] (No. 1)
[0241] (a) Preparation process
[0242] Cho Seong-sik 「Li」 1.04 Mn 0.6 Fe 0.4 Lithium hydroxide monohydrate, manganese carbonate, ferric phosphate, and lithium dihydrogen phosphate were weighed to have the composition ratio shown in PO4. Glucose was weighed at a mass fraction of 8% relative to the total mass of the raw materials. A slurry (first slurry) was formed by mixing the weighed materials with water. The solid content concentration of the first slurry was as shown in FIG. 6. Wet grinding was performed so that the D50 was 0.30 μm.
[0243] Secondary particles were formed by spray drying the first slurry. The target value of D50 of the secondary particles was 9±1 μm. The intake port temperature was as shown in Fig. 6. In addition, the exhaust port temperature of the spray dryer was 115±15℃, the spray rate was 10 mL / min, the intake pressure was 2.0 MPa, and the nozzle pressure of the spray nozzle was 0.2 MPa.
[0244] LMFP was synthesized by calcining secondary particles under a nitrogen atmosphere. Figure 7 shows the temperature profile during calcination. First, the furnace temperature is raised to 200°C at a heating rate of 3°C / min. The furnace temperature is maintained at 200°C for 1 hour. Next, the furnace temperature is raised to 650°C at a heating rate of 5°C / min. The furnace temperature is maintained at 650°C for 5 hours. After that, the furnace temperature is cooled to 400°C at a cooling rate of 2°C / min. Additionally, the furnace temperature is cooled to room temperature at a cooling rate of 15°C / min. Furthermore, in No. 1, the (b) contact process was not performed.
[0245] (c) Mixing process
[0246] A mixture was formed by mixing the obtained LMFP, conductive material (AB), binder (SBR), and thickener (CMC). The mixing ratio (mass ratio) was “LMFP / conductive material / binder / thickener = 96 / 1.5 / 2 / 0.5”. A slurry (second slurry) was formed by dispersing the mixture in water.
[0247] (d) Coating process
[0248] The second slurry was applied to the surface of the Al foil.
[0249] (e) Drying process
[0250] A positive electrode layer was formed by drying the applied second slurry at 100°C. By adjusting the density of the positive electrode layer to 1.8 g / cm³ using a roll press, a positive electrode layer (positive electrode disc) including the first region and the second region was formed. A vacuum drying treatment was performed on the positive electrode disc at 120°C for 12 hours.
[0251] (Production of Coin Cells)
[0252] After drying, a disc sample (diameter: 14 mm) was extracted from the positive electrode disc by stamping.
[0253] A coin cell was assembled inside the glove box. The cell configuration is as follows.
[0254] Working electrode: Disc sample (positive electrode)
[0255] Opposite poles: Li Park
[0256] Separator: Polymer porous membrane
[0257] Electrolyte: "EC / DMC = 3 / 7 (volume ratio)", LiPF6 (1 mol / L)
[0258] (No. 2~No. 10)
[0259] As shown in Fig. 6, LMFP was manufactured in the same way as No. 1, except that each condition of the manufacturing method was changed.
[0260] (b) Filling process
[0261] A portion of the obtained LMFP was immersed in NMP for 12 hours. After immersion, NMP attached to the surface of the LMFP was removed by performing suction filtration, solid-liquid separation, and washing.
[0262] (c) Mixing process
[0263] The obtained LMFP (NMP-containing LMFP) and the LMFP not immersed in NMP (NMP-free LMFP) were mixed in the mass ratio shown in Fig. 6 (NMP-containing LMFP:NMP-free LMFP = A:B). A mixture was obtained by mixing these LMFPs with a conductive material, a binder, and a thickening material in the same ratio as No. 1. A second slurry was formed by dispersing the mixture in water.
[0264] After that, a positive electrode was manufactured by undergoing (d) a coating process and (e) a drying process, just like No. 1. Also, a coin cell was assembled, just like No. 1.
[0265] < Evaluation >
[0266] (measurement)
[0267] X and Y of each No. listed in Fig. 6 were calculated by the method described above.
[0268] < Evaluation >
[0269] (Rate characteristics)
[0270] The discharge capacity ratio (1 C / 0.1 C) was measured by the following procedure. It is believed that the higher the discharge capacity ratio (1 C / 0.1 C), the better the rate characteristics.
[0271] A rate equivalent to 1 C is determined based on the discharge capacity (theoretical capacity) obtained from the coated mass of the positive electrode layer. "C" is a symbol representing the rate of current (time rate). At a rate of 1 C, the theoretical capacity is flowed over one hour. A coin cell is charged under a temperature environment of 25°C by constant current-constant voltage (CCCV) charging under the following conditions.
[0272] Rate during CC charging: 0.1 C
[0273] Charging upper limit voltage: 4.3 V
[0274] Cut-off current rate during CV charging: 0.01 C
[0275] After charging, the discharge capacity (0.1 C) (mAh / g) is measured by performing CC discharge to 3.0 V at a rate of 0.1 C. Again, the coin cell is charged by the above CCCV charging. After charging, the discharge capacity (1 C) is measured by performing CC discharge to 3.0 V at a rate of 1 C. The discharge capacity ratio (1 C / 0.1 C) is obtained by dividing the discharge capacity (1 C) by the discharge capacity (0.1 C). The result is shown in FIG. 6. In addition, the value of the rate characteristic in FIG. 6 is a relative value when the discharge capacity ratio of No. 1 is set to 100.
[0276] (Gas generation amount)
[0277] The amount of gas generated was measured by the following procedure.
[0278] Under a temperature environment of 60°C, 100 cycles of CC charging and discharging were performed at a rate of 0.1 C. The charging and discharging conditions were as described above. By the Archimedes method, under a temperature environment of 25°C, the volume of the coin cell before the start of charging and discharging and after 100 cycles was measured. The amount of gas generated was measured by subtracting the volume before the start of charging and discharging from the volume after 100 cycles. The results are shown in Fig. 6. Furthermore, the value of the amount of gas generated in Fig. 6 is a relative value when the amount of gas generated by No. 5 is set to 100.
[0279] < Result >
[0280] As shown in Figure 6, when the relationship 50% ≤ X is satisfied, the rate characteristics tend to improve. Also, when the relationship 60% ≤ X is satisfied, the rate characteristics tend to improve even more.
[0281] When the relationship 40%≤Y≤95% is satisfied, the amount of gas generated tends to decrease. Also, when the relationship 60%≤Y≤80% is satisfied, the amount of gas generated tends to decrease even more.
[0282] Although embodiments of the present invention have been described, the embodiments disclosed herein should be considered as illustrative and not limiting in all respects. The scope of the present invention is defined by the claims, and all modifications within the meaning and scope equivalent to the claims are intended to be included.
Claims
Claim 1 An electrode comprising a current collector foil and a positive electrode layer, wherein the positive electrode layer is disposed on the surface of the current collector foil, the positive electrode layer comprises a positive electrode active material, the positive electrode active material comprises a plurality of secondary particles, each of the plurality of secondary particles comprises a plurality of primary particles, the secondary particles comprise a vacancy particle having a vacancy, the cross-section of the positive electrode layer comprises a first region and a second region, the first region and the second region are distinguished by the cross-section of the positive electrode layer being divided into two equal parts in the thickness direction, the first region is disposed between the current collector foil and the second region, the relationship 50% ≤ X is satisfied, the X represents the ratio of the vacancy particle included in the first region to the vacancy particle included in the first region and the second region, and the X is calculated for the vacancy particle having a maximum ferret diameter of 5 μm or more. Claim 2 An electrode in which the relationship 60% ≤ X is satisfied in claim 1. Claim 3 An electrode according to claim 1, wherein the pore particles include open pore particles in which the pores are open to the outside, the relationship 40% ≤ Y ≤ 95% is satisfied, Y represents the ratio of the open pore particles to the pore particles, and Y is calculated for the pore particles having a maximum ferret diameter of 5 μm or more. Claim 4 An electrode in which the relationship 60%≤Y≤80% is satisfied in Clause 3. Claim 5 In claim 1, each of the plurality of primary particles comprises an olivine-type phosphate compound, forming an electrode. Claim 6 In claim 5, the electrode, wherein the olivine-type phosphate compound is lithium iron manganese phosphate. Claim 7 A battery comprising an electrode described in any one of claims 1 to 6. Claim 8 In claim 7, a battery having a bipolar structure. Claim 9 A method for manufacturing an electrode comprising: (a) preparing a positive electrode active material; (b) contacting at least a portion of the positive electrode active material with a first solvent; (c) forming a slurry by mixing the positive electrode active material after contact with the first solvent and a second solvent; (d) applying the slurry to the surface of a current collector foil; and (e) forming a positive electrode layer by drying the slurry, wherein the positive electrode active material comprises a plurality of secondary particles, the secondary particles comprise pore particles having vacancies, and the first solvent has a higher boiling point compared to the second solvent. Claim 10 A method for manufacturing an electrode according to claim 9, wherein, in (c) above, the positive electrode active material after contact with the first solvent and the positive electrode active material not contacted with the first solvent are weighed in a mass ratio of 1:0 to 1:2 and mixed with the second solvent. Claim 11 A method for manufacturing an electrode according to claim 9 or 10, wherein the first solvent comprises N-methyl-2-pyrrolidone and the second solvent comprises water.
Citation Information
Patent Citations
All-solid state battery
JP2012104270A
Lithium iron phosphate having olivine structure and method for preparing the same
KR1020100044713A
Secondary battery
KR1020130087038A
Anode active material with improved electrolyte wetting for lithium secondary battery and the prepattion method thereof
KR1020170016711A
Power storage element and all-solid-state secondary battery
WO2024135357A1
